2021
DOI: 10.1186/s41021-021-00186-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric profiling of DNA adducts in the human stomach associated with damage from environmental factors

Abstract: Background A comprehensive understanding of DNA adducts, one of the most plausible origins of cancer mutations, is still elusive, especially in human tissues in clinical settings. Recent technological developments have facilitated the identification of multiple DNA adducts in a single experiment. Only a few attempts toward this “DNA adductome approach” in human tissues have been reported. Geospatial information on DNA adducts in human organs has been scarce. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Reductions in 5hmdC levels in the non-tumoral portion of patients with malignant tumors have been reported in other diseases. We previously demonstrated that the global levels of 5hmdC were lower in the non-tumor gastric mucosa of gastric cancer patients than in control gastric mucosa [ 10 ]. Other pathological changes in non-tumoral tissue have also been detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in 5hmdC levels in the non-tumoral portion of patients with malignant tumors have been reported in other diseases. We previously demonstrated that the global levels of 5hmdC were lower in the non-tumor gastric mucosa of gastric cancer patients than in control gastric mucosa [ 10 ]. Other pathological changes in non-tumoral tissue have also been detected.…”
Section: Discussionmentioning
confidence: 99%
“…DNA adducts in human tissue have been investigated as the cause of DNA mutations in the lungs and gastrointestinal tract, which are directly exposed to potential procarcinogens and mutagens derived from environmental substances, such as tobacco smoke, polluted air, alcohol, and dietary carcinogens. Thus, the DNA lesions caused by these environmental constituents have been detected in the lungs and gastrointestinal tract [ 7 10 ]. The urinary system, which is constantly exposed to urine containing hydrophilic phase II metabolites, is another organ that is exposed to many environmental mutagens.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, we have reported an interindividual variance in the accumulation of DNA adducts in human gastric mucosae [57]. Although we also showed that the intraindividual difference in DNA adducts was small, we reanalyzed all the available data according to their anatomical information.…”
Section: Mass Spectrometric Profiling Of Dna Adducts In the Local Part Of The Human Stomachmentioning
confidence: 96%
“…To further explore the DNA adducts observed in the human stomach, we analyzed gastric mucosae resected from gastric cancer or non-gastric cancer patients using widetargeted identification of DNA adducts by liquid chromatography coupled with mass spectrometry [57]. We identified seven DNA adducts including modified bases, C5-methyl-2 -deoxycytidine, 2 -deoxyinosine, C5-hydroxymethyl-2 -deoxycytidine, N6-methyl-2deoxyadenosine, 1,N6-etheno-2 -deoxyadenosine, N6-hydroxymethyl-2 -deoxyadenosine, and C8-oxo-2 -deoxyguanosine, in the human stomach.…”
Section: Mass Spectrometric Profiling Of Dna Adducts In the Human Stomach Associated With Damage From Environmental Factorsmentioning
confidence: 99%
“…For example, applying a nontargeted 'omics' approach, thousands of potential DNA adduct m/z features were observed in human tissues such as lung, bronchia or saliva [86][87][88]. A challenging task will be to accurately identify the low abundant DNA adducts resulting from exogenous sources that are dwarfed by epigenic marks and endogenous DNA adducts, that are present at levels several orders of magnitude higher [89,90].…”
Section: Dna Adductomicsmentioning
confidence: 99%